Digital Accounting Transformation and Its Impact on the Financial Performance of MSMEs in Bogor Regency - Neny Hidayah Nur Imani; Ghita Freshilia (Pasundan Social Science Development, 2026)
The digital transformation of financial and accounting practices has fundamentally restructured the operational paradigms of Micro, Small, and Medium Enterprises (MSMEs) within emerging economies. Grounded in the Resource-Based View (RBV) theory, this extensive research investigates the distinct impacts of internal digital accounting systems and external digital payment integrations, specifically the Quick Response Code Indonesian Standard (QRIS), on the financial performance of MSMEs in Bogor Regency, West Java, Indonesia. Despite robust governmental initiatives to digitize the grassroots economy, a persistent accountability gap restricts nearly 60–70% of Indonesian MSMEs from accessing formal credit due to substandard financial reporting. Utilizing a quantitative survey design, empirical data was collected from 396 MSME owners across Bogor Regency's 40 districts, proportionally representing a total population of 35,542 registered enterprises. The research deploys Partial Least Squares Structural Equation Modeling (PLS-SEM) to rigorously assess both the measurement and structural models, applying contemporary thresholds for composite reliability and discriminant validity via the Heterotrait-Monotrait (HTMT) ratio. The empirical results demonstrate that the adoption of digital accounting applications—specifically free, cash-basis platforms such as SI APIK—significantly and positively impacts financial reporting quality and overall financial performance. Conversely, the impact of digital payments presents an economic paradox; while QRIS enhances transaction efficiency and market access, its positive effect on financial performance is partially suppressed by administrative friction, specifically the Merchant Discount Rate (MDR) fees and settlement time lags, which constrain the daily capital turnover of micro-enterprises. Furthermore, structural compliance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) acts as a crucial mediating mechanism, transforming digital platform capabilities into tangible financial outcomes and institutional bankability. These findings provide vital policy implications for regional authorities seeking to accelerate financial inclusion and optimize digital literacy programs beyond mere payment adoption.